Tetracyclines uptake from irrigation water by vegetables: Accumulation and antimicrobial resistance risks - Gudda, Fredrick; Odinga, E.S.; Tang, L.; Waigi, M.G.; Wang, J.; Abdalmegeed, D.; Gao, Y. (Elsevier, 2023)
Wastewater irrigation may introduce antibiotic residues in the soil-plant systems. This study aimed to investigate the uptake of tetracyclines by spinach and collard greens and assess associated ecological and human health risks. Synthetic wastewater spiked with 1 ppm and 10 ppm of oxytetracycline, doxycycline, and tetracycline was used to grow vegetables in a greenhouse pot experiment. The uptake and accumulation of the tetracyclines were low and residual concentrations in the soil were negligible. All the tetracyclines were detected at concentrations ranging from 1.68 to 51.41 μg/g (spinach) and 1.94–30.95 μg/g (collard greens). The accumulation rate was in a dose-response scenario with a bioconcentration factor of 6.34 mL/kg (spinach) and 2.64 mL/kg (collard greens). Oxytetracycline had the highest accumulation in leaves, followed by doxycycline and tetracycline, and the residual concentrations followed the same order. The highest residual concentration was in soils receiving 10 ppm oxytetracycline. Residual concentrations in the soil were lower than accumulated levels and exerted negligible ecological risks. Tetracyclines accumulation in spinach significantly differed between the vegetables demonstrating a subspecies difference in uptake and accumulation. Ecological risk quotient (RQ) and human health risk quotient (HQ) were below thresholds that would exert toxicity and resistance selection impacts. Although RQs and HQs are low (<0.1), this study shows that the vegetables accumulate tetracyclines from irrigation water, posing plausible human health risks to allergic individuals. Similarly, the ecological risks cannot be ignored because the synergistic and antagonistic effects of sublethal concentrations can perturb ecosystem processes.